2011
DOI: 10.1016/j.mambio.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Riverine refuging by proboscis monkeys (Nasalis larvatus) and sympatric primates: Implications for adaptive benefits of the riverine habitat

Abstract: a b s t r a c tRiverine refuging by non-human primates, with focus on proboscis monkeys, was studied in a forest along the Menanggul River, Sabah, Malaysia from May 2005 to 2006. The results of the primate census indicated that not only proboscis monkeys but also sympatric primates inhabiting the study site preferred to utilize the riverine habitat for night-time sleeping, though the frequency of riverine usage was different among these sympatric primates. Four predation-related events in the study site and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 23 publications
(26 reference statements)
1
45
1
Order By: Relevance
“…In riverine forests, proboscis monkeys are known to take refuge along riverbanks to spend the night [Matsuda et al, 2011b]. During this study, we conducted boat-based surveys along the Kinabatangan River, in the late afternoon, to find proboscis monkey groups settled at their sleeping sites.…”
Section: Faecal Samplingmentioning
confidence: 99%
“…In riverine forests, proboscis monkeys are known to take refuge along riverbanks to spend the night [Matsuda et al, 2011b]. During this study, we conducted boat-based surveys along the Kinabatangan River, in the late afternoon, to find proboscis monkey groups settled at their sleeping sites.…”
Section: Faecal Samplingmentioning
confidence: 99%
“…This choice may reflect an antipredator strategy, as suggested for proboscis monkeys [Matsuda et al, 2008[Matsuda et al, , 2011. The presence of the river along one side of the sleeping site decreases the area of ground needing monitoring and also lowers the probability of being surprised by a predator approaching from the ground.…”
Section: Predationmentioning
confidence: 99%
“…In addition, we expected a regular change of their sleeping sites to prevent a predator from learning about the reuse of sleeping sites. Finally, we expected macaques to choose trees in particular locations making the site safer, such as near a river as shown in several species of primates, including pigtailed macaques [Matsuda et al, 2008[Matsuda et al, , 2011. Following the MCPF hypothesis, we predicted that the sleeping sites, as central places, should be close to the last or first feeding tree of the day to minimize travel costs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have conducted foot-based transects or point surveys for primates in Bornean flooded forests, e.g., orangutan (Pongo pygmaeus; with a focus on their nests), red leaf monkey (Presbytis rubicunda), silver langur (Presbytis cristata), proboscis monkey (Nasalis larvatus), long-tailed macaque (Macaca fascicularis), pig-tailed macaque (M. nemestrina), and/or gibbon (Hylobates spp.) Ancrenaz et al 2004;Buckley et al 2006;Cheyne et al 2008;Matsuda et al 2009;Matsuda et al 2011;Ehlers Smith and Ehlers Smith 2013). Foot-based surveys are difficult to conduct in swampy habitats; therefore, boat-based surveys have been performed to census endangered proboscis monkeys, Hose's langur (Presbytis hosei), maroon langur (Pr.…”
mentioning
confidence: 99%
“…However, the sensitivity of these methods and the accuracy of the animal counts obtained have not been assessed. Matsuda et al (2011) performed foot-based transect surveys through a Bornean riverine forest and showed that several primate species such as proboscis monkeys, silver langurs, long-tailed macaques, pigtailed macaques, gibbons, and orangutans were frequently encountered <50 m from the river. However, these results have not yet been compared with those obtained from boat-based surveys at the same study site.…”
mentioning
confidence: 99%